Introduction to MANAGEMENT ACCOUNTING - Horngren, Charles T.; Sundem, Gary L.; Burgstahler, David; Schatzberg, Jeff (Pearson Education Limited, 2023)
Introduction to Management Accounting helps to enhance students’ ability to make effective economic decisions by encouraging them to understand the inner-workings of the concepts, rather than solely focusing on technique memorization. Overall, this text describes both theory and common practices in a way that will help students produce information that’s useful in day-to-day decision-making